FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN INDEKS LQ45 PERIODE 2017-2022 - Hidayatullah, Wildan Widya; Anggraeni, Anggraeni (Jurnal Ilmiah Global Education, 2023)
This study aims to examine and analyze the effect of capital structure, liquidity, ownership structure and company size on stock prices of LQ45 Index companies on the Indonesia Stock Exchange for the 2017-2022 period. The independent variables in this study are capital structure (DER), liquidity (Cash ratio), ownership structure (KI and KM) and company size (SIZE). The population of this study is nonbanking and financial sector companies that are consistently listed on the LQ45 Index for the 2017-2022 period. The research sampling technique used purposive sampling, the number of samples was 10 companies. The analysis technique in this study used multiple linear regression analysis. The results of this study indicate Ownership structure as measured by Managerial Ownership (KM) has no significant negative effect on stock prices and Company size measured using (SIZE) has a significant effect on stock prices. Capital structure, liquidity, ownership structure, and company size simultaneously influence stock prices. The magnitude of the influence of the independent variables simultaneously on stock prices.